Differences in performance, carcass characteristics and meat quality between fast- and slow-growing broiler genotypes - Canoğulları Doğan, Sibel; Baylan, Mikail; Bulancak, Ayşen; Ayaşan, Tugay (Progress in Nutrition, 2019)
This study was conducted to determine the differences in performance, carcass characteristics and meat quality between fast- and slow-growing broilers. Ross-308 genotype was used as the fast-growing genotype, while local T2-Y2 genotype was used as the slow-growing genotype. The study continued until both genotypes reached acceptable market weight (2 kg). Both genotypes consisted of 4 subgroups, each containing 50 broiler chicks. Fast-growing broilers reached market weight (2 kg) on day 38, while slow-growing broilers reached the same weight on day 72. Fast-growing broilers consumed less feed to attain 2 kg live weight compared with slow-growing broilers. The feed conversion ratio of the fast-growing broilers was 1.63, while that of the slow-growing broilers was 2.67. Significant differences were observed between the genotypes with regard to the percentage weights of the gizzard, liver, leg and breast. The percentage weights of the leg and abdominal fat were higher in slow-growing broilers, while the percentage weight of the breast was higher in fast-growing broilers. No difference was observed between the genotypes with regard to cooking loss in leg and breast meats, whereas differences were recorded with regard to the water holding capacity (%) in leg meat. The slow-growing genotype had lower pH values in breast and leg meats. The values of leg meat brightness (L*), redness (a*) and yellowness (b*) were higher in the slow-growing broilers, but the differences were not statistically significant. The L* and a* values of breast meat were found to be higher in slow-growing broilers. These results showed that in the slow-growing genotype, breast and leg meat color L, a and b value are enhanced. However, the fast-growing genotype has better performance and carcass characteristics compared to the slow-growing genotype.